EVALUATION OF CERTAIN INSECTICIDES AGAINST SPOTTED POD BORER [MARUCA VITRATA (GEYER)] ON MUNGBEAN (VIGNA RADIATA L.) - BIRBAL BAIRWA; P. S. SINGH (The Bioscan, 2015)
Present study was conducted at Agricultural Research Farm, Banaras Hindu University, Varanasi during Kharif season of 2013 and 2014 to know the efficacy of certain newer group of insecticides (Indoxacarb 14.5% SC, Spinosad 45% SC, Lambda cyhatlothrin 5% EC, Profenophos 50% EC, Imidacloprid 17.8% SL, Emamectin benzoate 5% SG, Thiamethoxam 25% WG, Bperofezine 25% SC and Clothianidin 50% WDG) against spotted pod borer (Maruca vitrata) on mungbean. In Kharif season of 2013and 2014Indoxacarb 14.5% SC, Spinosad 45% SC and Profenophos 50% EC were the most effective treatments and significantly superior to other treatment with 75.04, 73.02 and 68.50 % larval population reduction with maximum yield of mungbean i.e.,8.09, 9.06 and 8.59q/ha respectively, over control. The least effective treatment was Buprofezine 25% SC followed by Clothianidin 50% WDG with 40.87 and 38.66 % reduction in larval population and minimum yield of mungbeani.e.,8.13 and 8.55q/ha, respectively, over control.